( 0 2 0 1 7 ) − ( 1 2 0 1 6 ) + ( 2 2 0 1 5 ) − ( 3 2 0 1 4 ) + ⋯ + ( 1 0 0 8 1 0 0 9 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What would be the answer if I replace all negative signs with positive signs?
Can you elaborate from the 'characteristic equation' ? What does it mean and how did you get this ?
We could do it without recurrence relations too though it gets a bit tedious. Great problem!
Fabulous..
Problem Loading...
Note Loading...
Set Loading...
Let us define
S n = ( 0 n ) − ( 1 n − 1 ) + ⋯ + ( − 1 ) ⌊ n / 2 ⌋ ( ⌊ n / 2 ⌋ n − ⌊ n / 2 ⌋ )
For n = 2 m ,
S 2 m = ( 0 2 m ) − ( 1 2 m − 1 ) + ⋯ + ( − 1 ) m ( m m )
S 2 m − 1 = ( 0 2 m − 1 ) − ( 1 2 m − 2 ) + ⋯ + ( − 1 ) m − 1 ( m − 1 m )
S 2 m − 2 = ( 0 2 m − 2 ) − ( 1 2 m − 3 ) + ⋯ + ( − 1 ) m − 1 ( m − 1 m − 1 )
Therefore,
S 2 m − 1 − S 2 m − 2 = ( 0 2 m − 1 ) − ( 1 2 m − 1 ) + ( 2 2 m − 2 ) − ⋯ + ( − 1 ) m − 1 ( m − 1 m + 1 ) − ( − 1 ) m − 1 ( m − 1 m − 1 )
Since ( 0 2 m − 1 ) = ( 0 2 m ) ,
S 2 m − 1 − S 2 m − 2 = S 2 m − ( − 1 ) m ( m m ) − ( − 1 ) m − 1 ( m − 1 m − 1 )
S 2 m − 1 = S 2 m + S 2 m − 2
For n = 2 m + 1 ,
S 2 m + 1 = ( 0 2 m + 1 ) − ( 1 2 m ) + ⋯ + ( − 1 ) m ( m m + 1 )
S 2 m = ( 0 2 m ) − ( 1 2 m − 1 ) + ⋯ + ( − 1 ) m ( m m )
S 2 m − 1 = ( 0 2 m − 1 ) − ( 1 2 m − 2 ) + ⋯ + ( − 1 ) m − 1 ( m − 1 m )
S 2 m − S 2 m − 1 = ( 0 2 m ) − ( 1 2 m ) + ⋯ + ( − 1 ) m ( m m + 1 )
S 2 m − S 2 m − 1 = S 2 m + 1
S 2 m = S 2 m − 1 + S 2 m + 1
Hence, our recurrence relation for S n becomes,
S n = S n − 1 + S n + 1 , n ≥ 2
S 1 = 1 , S 2 = 0
Characteristic equation becomes - x 2 − x + 1 = 0
⟹ S n = A z n + B z − n , where z = 2 1 + 3 ι = e i π / 3
S 1 = A e i π / 3 + B e − i π / 3 = 1
S 2 = A e 2 i π / 3 + B e − 2 i π / 3 = 0
⟹ A = 1 + e i π / 3 1 , B = 1 + e i π / 3 e i π / 3
S n = 1 + e i π / 3 e n i π / 3 + 1 + e i π / 3 e ( 1 − n ) i π / 3
S n = 3 sin ( 3 n π ) + cos ( 3 n π )